Friends, enemies - Rushton, Rosie (New York : Hyperion, 2004)
When fourteen-year-old Tory and her circle reluctantly befriend Hannah, they uncover deceit and hidden family crises.
Previously published under the title "Friends, enemies, and other tiny problems" in Great Britain, 2003.
Keywords: Interpersonal relations; Friendship; Honesty